2021
DOI: 10.3389/fnrgo.2021.768386
|View full text |Cite
|
Sign up to set email alerts
|

Style Features in Communication of the Crews With Mission Control

Abstract: In “Content,” an International Space Station (ISS) Russian segment space experiment, features of communication between the cosmonauts and the Mission Control Center (MCC) were studied using content analysis. The method is based on the concept of stress copings by Lazarus and Folkman. Differences found in the communication of cosmonauts led to assumptions about the existence of individual communication styles in routine communication between the cosmonauts and the MCC. The differences found were defined using V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In this chapter, we present a summary of the main results obtained within the frame of "Content" space experiment (Yusupova et al, 2019(Yusupova et al, , 2021(Yusupova et al, , 2022a(Yusupova et al, , 2022b, from 15 ISS missions.…”
Section: Resultsmentioning
confidence: 99%
“…In this chapter, we present a summary of the main results obtained within the frame of "Content" space experiment (Yusupova et al, 2019(Yusupova et al, , 2021(Yusupova et al, , 2022a(Yusupova et al, , 2022b, from 15 ISS missions.…”
Section: Resultsmentioning
confidence: 99%
“…In tense operating conditions, astronauts mobilize their psychological resources and apply their usual models of responding to problematic situations and resolving them in the context of interaction in communication with the MCC. Astronauts assess and cope with stressful situations of space flight in accordance with their personal characteristics, which determine the choice of coping strategies within a certain style of communicative behavior and depending on the communication functions prevailing in this style (exchange of information, exchange of emotions, and social regulation [6,10]). Different types and sets of coping strategies, however, have different effectiveness in remote joint activities.…”
Section: Discussionmentioning
confidence: 99%
“…A further comparison in the type of dominating coping strategies was made between the groups. In our previous studies, we showed that one of the three Satir styles ("computing", "blaming", or "placating") usually dominates in an astronaut's speech [10]. This content analysis method was also successfully used to study the crew-MCC communications in a series of IBMP-based model experiments (SIRIUS) [18].…”
Section: Content Analysis Criteriamentioning
confidence: 99%
“…A 40-min delay is the setting of a Martian journey. Increasing or decreasing levels in data reports or style of communication, as in the International Space Station (Yusupova et al, 2021), can be interpreted as negative outputs but used for positive inputs in the crew support onboard. New countermeasures, such as virtual reality technologies, voice assistant technologies and social robots are key insights to compensate for sensory deprivation and interrelationship limitations (Gushin et al, 2021).…”
mentioning
confidence: 99%